Las relaciones internacionales entre colombia y brasil: analisis y evaluacion de la comision fronteriza (2012)
An analysis of the relations was realized between Colombia and Brazil, from the perspective of the tools of integration implemented by Colombia to fulfill aims of exterior politics there are created the binational commissions that seek to improve the living conditions of the inhabitants of the common border and to promote the generation of an axis of development that allows to Colombia the regional integration and the cooperation from the resolution of problematic common, comparing the principal binational commissions of Colombia, with Venezuela, Ecuador, Peru and Brazil, identifying the most effective policitics, and the priority failings, to establish recommendations towards the attainment of the aims proposed by the commission. There are highlighted the achievements obtained by the commissions and the obstacles that each one presents and they propose strategies that carry the integral development of the population in the border with Brazil, including important aspects as the environment, in this case the Colombian amazonia. There is evaluated also the management of the state, which in its policies proposes support to the borders and development from them, but the reality is far from what is established, since the commission does not have sufficient scope to achieve the established goals, principally because the Amazonian border is much more relegated that other borders; this condition assumes him to the difficulties of access and the proliferation of the armed conflict and the corruption in this region.